PENGARUH KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Euis Ajizah; Bagas Oke Perdinusa (Universitas La Tansa Mashiro, 2022)
Company value can show the value of assets owned by the company such as securities. Firm value is very important, because it reflects the company's performance which can affect investors' perceptions of the company. The value of the company will show the prosperity of shareholders. The higher the value of the company, the more prosperous the shareholders. Based on the results of research on dividend policy and debt policy on firm value, it can be concluded that partially the dividend policy has a significant effect. Because, the calculated t value is greater than t table. So it can be concluded that dividend policy has a significant effect on firm value in LQ45 index companies listed on the Indonesian Stock Exchange (IDX). Partially it can be concluded that debt policy has no significant effect. Because. The value of t table is greater than t count. Therefore it can be concluded that debt policy has a significant negative effect on firm value in LQ45 index companies listed on the Indonesia Stock Exchange (IDX). Simultaneously dividend policy and debt policy obtain a calculated F value greater than F table. So, it can be concluded that simultaneously dividend policy and debt policy have a significant effect on firm value in LQ45 index companies listed on the Indonesia Stock Exchange (IDX)..